Milk flavor quality on the farm - H.A. Roberts (Kansas Agricultural Experiment Station Research Reports, 1986)
Milk consumption is influenced by the quality and flavor of the milk a person drinks. Today the consumer evaluates milk solely on its taste and keeping quality. Since the flavor of milk cannot be improved after it leaves the dairy farm, it is of the utmost importance to produce milk with the best flavor quality possible. Milk is a highly perishable food and must be produced under conditions that will ensure keeping quality. Generally speaking, dairymen are doing a good job of producing high quality milk but we need to be aware that problems may occur with feeding, cow health, cleaning, sanitizing and general handling of the milk. It is important to know what is good tasting milk and then use this standard to produce top quality milk free of off flavors. Following are brief discussions regarding some of the milk flavor problems that still exist today, with suggestions on how to reduce these problems.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Milk flavor; Flavor; Milk consumption